Sensitivity study on influencing parameters of transformer thermal model with directed oil flow - Nik Supian, Nik Mohd Azri (2013)
The thermal design of a power transformer has to keep the temperature within limits according to international agreement standards. Two of the limits are a maximum temperature rise and a maximum oil temperature. The purpose of this study was to study the temperature distributions and oil velocity inside coil of the power transformer and to model and develop a program using MATLAB that can modulate the suitable parameter that not exceeds maximum temperature rise in disk coil transformer. Two methods have been used to study the velocity and temperature parameters affecting the oil flow through the transformer. The first approach focused on equation derived from previous worked about oil flow and temperature distribution. The second approach was to handle the problem as a global optimization problem solved by numerical methods. The optimization was done using predictions from a program used for velocity and temperature calculation. The numerical method result was successful; on all the designs tested it gave a lower temperature rise value according to international agreement standards. Test the program by using different value in the parameter have been tested on sensitivity of study. The study has shown that a geometrical detail approach provided for better design solutions in reasonable time and therefore has shown its potential for practical use. Both the methods could be combined and used for further investigation.